2021
DOI: 10.1192/bjo.2021.24
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of COVID-19 dissemination on symptoms of anxiety and depression among university students

Abstract: Background Evidence about the impact of the COVID-19 pandemic on the mental health of specific subpopulations, such as university students, is needed as communities prepare for future waves. Aims To study the association of proximity of COVID-19 with symptoms of anxiety and depression in university students. Method This trend study analysed weekly cross-sectional surveys of probabilistic samples of students from the University of British Columbia for 13 weeks, through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
6
25
0
Order By: Relevance
“…This will require appropriate training and the availability of psychological and emotional support. Additional care will also be required for those students who proved unable to access help [ 45 ]. It seems essential to mobilize, extend, implement and perpetuate in the long term, within the institutions themselves, services working for the well-being of students, reinforced coaching systems, and systematic recourse to available aid (thus promoting the destigmatization of young people in difficulty).…”
Section: Discussionmentioning
confidence: 99%
“…This will require appropriate training and the availability of psychological and emotional support. Additional care will also be required for those students who proved unable to access help [ 45 ]. It seems essential to mobilize, extend, implement and perpetuate in the long term, within the institutions themselves, services working for the well-being of students, reinforced coaching systems, and systematic recourse to available aid (thus promoting the destigmatization of young people in difficulty).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the patients specifically identified a link between these media exposures and the onset of symptoms, although, with some of the younger children, the social media use was only disclosed after careful questioning. The COVID-19 pandemic has been a major source of stress and anxiety for people around the world, resulting in increased mental health symptoms and demand for mental health services (14)(15)(16)(17)(18). Increased social isolation and the widespread utilization of social media may have contributed as precipitating factors in a relevant proportion of these patients.…”
Section: Accepted Articlementioning
confidence: 99%
“…The COVID‐19 pandemic has been a major source of stress and anxiety for people globally, resulting in increased mental health symptoms and demand for mental health services. 14 , 15 , 16 , 17 , 18 Increased social isolation and the widespread utilization of social media may have contributed as precipitating factors in a relevant proportion of these patients. External factors like watching popular social media personalities' videos portraying tics or tic‐like behaviors may have instilled a belief that “tics” may catalyze peer acceptance or even popularity.…”
Section: Viewpointmentioning
confidence: 99%
“…Students also shifted their main concerns from learning-related to financial and/or health-related matters [46]. Recent studies showed that exposure to COVID-19-related mat-ters may increase the risk of anxiety symptoms in students (particularly among men) [47]. Physical activity constitutes the next key predictor of mental health problems.…”
Section: Introductionmentioning
confidence: 99%